Comparison of emergency physician opinions with MSOFA and PREMEWS scores in determining the necessity of non-traumatic internal medicine patient transfers to the emergency department: a longitudinal study - Abbasali Ebrahimian; Ali Fakhr-Movahedi; Mohammad Taghi Shahcheragh; Seyyed Hossein Shahcheragh (BMC Emergency Medicine)
Abstract Background Accurate prehospital decision-making is critical in emergency care to ensure the appropriate use of resources and optimal patient outcomes. However, the alignment between emergency physicians’ clinical judgments and scoring systems such as Prehospital Modified Early Warning Score (Pre-MEWS) and the modified Sequential Organ Failure Assessment (mSOFA) remains underexplored. Objective This study investigates the consistency of prehospital Pre-MEWS and in-hospital mSOFA scores with emergency physicians’ judgments in determining the necessity of non-traumatic Internal Medicine Patient transfers to emergency departments (EDs). Additionally, it evaluates the clinical outcomes of these transfers. Methods In this longitudinal study conducted between 2019 and 2020 in Semnan, Iran, 675 non-traumatic Internal patients transferred to a single ED were analyzed. Pre-MEWS scores were recorded prehospital, while mSOFA scores and physicians’ evaluations were documented post-transfer. Outcomes included discharge, hospital admission, ICU transfer, or death. Results This study analyzed 675 non-traumatic Internal patients transferred to the emergency department, with a mean age of 55.93 ± 21.89 years. 31% of transfers were deemed unnecessary by emergency physicians. The mean length of stay was 5.63 ± 5.69 h, showing a significant correlation with higher Pre-MEWS and mSOFA scores (p < 0.0001). Based on Pre-MEWS, patients were stratified into three risk levels: Green (≤ 3, no ICU/mortality), Yellow (4–12, 3.8% ICU admissions, no deaths), and Red (≥ 13, all deceased patients). mSOFA scoring identified two risk levels: Yellow (1–5, 0% mortality, ICU risk rising to 20%) and Red (≥ 6, ICU admissions up to 100%, mortality risk reaching 676.8%). Specifically, all deceased patients had Pre-MEWS scores ≥ 13, and ICU admission was observed in 3.8% of patients with Pre-MEWS scores between 4 and 12. The mSOFA score demonstrated superior predictive accuracy for mortality and ICU admission compared to Pre-MEWS. However, Pre-MEWS provided practical utility for prehospital triage. Conclusion Combining scoring systems with clinical judgment can improve decision-making in prehospital settings. Enhanced integration of tools and expertise is recommended to reduce unnecessary transfers and optimize emergency care.